HEALTH AND PHYSIOLOGICAL POTENTIAL OF SOYBEAN SEEDS SUBMITTED TO DIFFERENT STORAGE CONDITIONS - Querales, Pastora Josefina; Forti, Victor Augusto; Frare, Vanessa Cristina; Pinto, Taís Leite Ferreira; Tremocoldi, Annelise Roberta; Malaguetta, Heloisa; Martins, Thaïs Dias; de Moraes, Maria Heloisa Duarte (REVISTA DE AGRICULTURA, 2016)
The objective of this study was to verify the health and physiological potential of soybean seeds submitted to different storage conditions. Three batches of soybean seeds were first evaluated for their health and physiological quality with sanitary, germination, seedling emergence in a greenhouse and accelerated aging tests; moisture content was also determined. The seeds were stored for six months under cold chamber (temperature of 10°C and 85% RH), dry chamber (temperature of 20°C and 50% RH) and laboratory (uncontrolled) conditions. Seed samples were taken every three months and submitted to the tests mentioned previously. The harmful effect of fungi on seed quality before storage was observed. Generally, there was a reduction in fungal occurrence with storage, principally for the conditions of the cold chamber and the uncontrolled laboratory environment, resulting in the increased of germination and seedling emergence.